O papel da controladoria das empresas na avaliação dos investimentos em tecnologia da informação - Ogassavara, Tomio (2010)
Due to the economies and markets globalization, the information technology has increased its participation in all areas of business, creating new challenges for business management. On this context the controller responsible for providing and managing the information systems control and performance evaluation of the company needs to increase his participation on investment management of information technology. IT Governance has become well known, especially after Sarbanes-Oxley law has been implemented by organizations in order to gain better IT control management and attend demands from control´s organizations. This study aims to verify how the controller evaluates and manages IT investments, as well as his uses IT governance structure outlined in VAL IT. The research methodology used was qualitative research and exploratory-descriptive type. The data collections were used questionnaires and interviews. In questionnaire was used the Maturity Model. The research was conducted in European conglomerate business located in Mercosur operating on segments like plastics, chemicals and pharmaceuticals. The literature revision procedures applied in this study used literature research, documents, materials published in books, magazines, specialized dictionaries, theses, dissertations and internet